2015
DOI: 10.1016/j.jphs.2015.10.005
|View full text |Cite
|
Sign up to set email alerts
|

Chlorogenic acid protects against cholestatic liver injury in rats

Abstract: The aim of this study was to investigate the protective effect of chlorogenic acid (CA) on liver injury caused by bile duct ligation (BDL), as well as the potential mechanism. Permanent bile duct ligation induced liver injury was evaluated by liver index, liver function and pathological observation. Oral administration of CA for 3 weeks markedly attenuated liver swelling and fibrosis. Blood biochemistry results revealed that CA decreased alanine transaminase, aspartate aminotransferase, alkaline phosphatase, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…Artemisia capillaris (Yin‐Chen) is another commonly used traditional herb rich in CA . CA has been shown to alleviate liver injury induced by bile duct ligation (BDL) in rats and to decrease liver fibrosis through decreased expression of collagen I and III, transforming growth factors, and vascular epithelial growth factor . Nevertheless, the mechanisms involved in the choleretic effect of CA are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Artemisia capillaris (Yin‐Chen) is another commonly used traditional herb rich in CA . CA has been shown to alleviate liver injury induced by bile duct ligation (BDL) in rats and to decrease liver fibrosis through decreased expression of collagen I and III, transforming growth factors, and vascular epithelial growth factor . Nevertheless, the mechanisms involved in the choleretic effect of CA are not fully understood.…”
Section: Introductionmentioning
confidence: 99%
“…Serum alanine transaminase, AST, ALP, total bilirubin, direct bilirubin and total bile acid levels were decreased. Furthermore collagen I, collagen III, TGF-β1 and VEGF mRNA increasing induced by BDL treatment were also suppressed by chlorogenic acid [25] . Free radicals generated by CCl 4 metabolization via cytochrome P450 2E1 induce liver cell apoptosis and necrosis as well as upregulation of TNF-α, IL-10 and TGF-β in necrotic hepatocytes.…”
Section: Resultsmentioning
confidence: 85%
“…Wu et al reported that [25] chlorogenic acid administration at 75 mg/kg and 150 mg/kg dose for 3 w provided significant recovery in liver fibrosis induced by bile duct ligation. Serum alanine transaminase, AST, ALP, total bilirubin, direct bilirubin and total bile acid levels were decreased.…”
Section: Resultsmentioning
confidence: 99%
“…As shown in Figure 6 among these chemical markers, the geniposide, scopoletin, chlorogenic acid and 3,5-dicaffeoylquinic acid contents in the separated decoction is lower than in the combined decoction, whereas genipin and caffeic acid showed higher concentrations in the separated decoction than in the combined decoction. To our knowledge, genipin, chlorogenic acid, and caffeic acid can protect against liver injury [23][24][25], though no evidence suggests that scopoletin and 3,5-dicaffeoylquinic acid have hepatoprotective effects.…”
Section: Identification Of Chemical Markers and Comparison Of Hepatopmentioning
confidence: 99%